Sistem Pemanggil Pelayan LCLE (Low Cost Low Energy) berbasis ESP-NOW - Aulia Nabih Rizqullah; Agung Setia Budi; Rakhmadhany Primananda (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2023)
Waiters in restaurants often experience problems where the waiter sometimes does not hear customer orders properly so that errors occur in ordering, or problems where the waiter also does not hear when a customer calls the waiters. Therefore, service providers must improve services so that businesses can run optimally. One solution that can be done is take advantage of technological systems that were created to help overcome existing problems, is the use of an ESP-NOW-based communication protocol system. Therefore, in this study, a waiter calling system was created to be implemented a restaurant by implementing the ESP-NOW communication protocol technology. From the results of this study it is known that the use of ESP32 and ESP8266 can be considered efficient in terms of power usage because the test results obtained power consumption data with an average of 0.1087W for ESP8266 and 0.6932W for ESP32. The cost of assembling a complete set of ESP-NOW-based terminal systems is very affordable, namely Rp. 671,980, when compared to using a smart tablet device with an estimated cost of Rp. 24,440,000. The use of ESP32 and ESP8266 paired with the ESP-Now communication protocol is suitable as a low-cost, low-energy alternative for restaurant information system devices because it has low latency. The prototype used in this study was sufficient for the requirements specified at the beginning of the study.